Advanced Mathematical and Computational Tools in Metrology and Testing X - Pavese, Franco ... [et al.] (Singapore : World Scientific Pub. Co., 2015)
"This volume contains original and refereed contributions from the tenth AMCTM Conference (http://www.nviim.ru/AMCTM2014) held in St. Petersburg (Russia) in September 2014 on the theme of advanced mathematical and computational tools in metrology and testing. The themes in this volume reflect the importance of the mathematical, statistical and numerical tools and techniques in metrology and testing and, also keeping the challenge promoted by the Metre Convention, to access a mutual recognition for the measurement standards."--
Includes bibliographical references and indexes.
Electronic reproduction.
System requirements: Adobe Acrobat Reader required to view PDF file.
Mode of access: World Wide Web.
Keywords: Metrology; Statistics; Electronic books